Integrated Air Pollution Management in China : Developing Particulate Matter Control - World Bank (Washington, DC, 2012)
This study is a joint effort of the Ministry of Environmental Protection (MEP), Chinese experts, and the World Bank to inform the policy-making process in line with the government of China s medium- and long-term objectives. Specifically the study aims to assist MEP, provincial governments, and municipalities by: (1) Proposing a national PM10 compliance plan to help non-compliant cities attain grade II - preferably by 2015 or in certain cases by 2020 at the latest - and already compliant cities to further reduce PM concentrations. The plan would include (a) policies and regulations and associated physical interventions/measures; (b) geographical scope; (c) sequencing of interventions; and (d) feasible environmental investments likely to have high benefit/cost ratios. (2) recommending a PM2.5 monitoring system and related data applications.